MARKETING MANAGEMENT SYSTEM IMPLEMENTATION FOR MANUFACTURING FIRMS: REVIEW - Dr. C.P. Verma, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The traditional business management theory's view and type of competitiveness is that manufacturing and distribution efficiency is the main competitive aspect in production companies, with corporate managers mainly dealing with controlling inventory and handling external industries. But many business owners with conventional management experience think that the main role of such business is to purchase many advanced equipment and manufacturing technique to produce products of high quality that more like consumers, that is to say, business managers are concerned primarily with production management and external business management. Marketing tactics are the main key to success of manufacturing firm in tough competitive environment. Alternatively, little attention is paid to the brand strategy of these firms. Therefore, the paper devised a marketing system for manufacturing companies based on the new global competition situation and suggested a comprehensive implementation scheme to help them turn the conventional operational made of their manufacturing industries into informative made as easily as they could